2015
DOI: 10.4172/2161-038x.1000153
|View full text |Cite
|
Sign up to set email alerts
|

Menarche Age of Mothers and Daughters and Correlation between them in Saudi Arabia

Abstract: Objective: Menarche is the hallmark maturation event of every female child. The menarcheal age of mothers is thought to be a good predictor of the menarcheal age of daughters. The aim of this study is to evaluate the current age at menarche of young girls and to examine its correlation with that of mother's menarcheal age. Materials and methods: This was a questionnaire-based cross sectional study conducted at Jeddah in Saudi Arabia. The target study population included young girls between ages 12 and 16 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…This descriptive analysis is in line with that The mean menarche age for the mothers (12.97 ± 1.71 years) was significantly higher than the daughters (11.5 ± 1.48 years). But, that study has found a correlation between mothers' and daughters' age at menarche [42]. The results of this study are in line with research which states that there is no relationship between maternal age at menarche and respondent's age at menarche.…”
Section: The Effect Of Maternal Menarche On Menarche (Genetics)supporting
confidence: 89%
“…This descriptive analysis is in line with that The mean menarche age for the mothers (12.97 ± 1.71 years) was significantly higher than the daughters (11.5 ± 1.48 years). But, that study has found a correlation between mothers' and daughters' age at menarche [42]. The results of this study are in line with research which states that there is no relationship between maternal age at menarche and respondent's age at menarche.…”
Section: The Effect Of Maternal Menarche On Menarche (Genetics)supporting
confidence: 89%
“…A study in Al-karch side of Baghdad governorate showed the age of menarche 11.8±1.8 years (15) .In another study in Kuwait, it was 12.4 years (16). In a study of Saudi Arabia in 2014, the mean age of the menarche was 11.5 ± 1.48 years (17),In comparison with studies conducted in developed countries, this study results are agree with studies in Canada, mean age of menarche was 12.72 ± 1.05 years (18), and in the other study in the UK, the mean age of menarche was12.7 ±1.5 years (19).…”
Section: Discussionmentioning
confidence: 98%
“…Several studies have found an association between menarche age and psychological factors, genetics, socioeconomic status, physical activity, the presence of chronic diseases, diet, maternal and child factors such as weight, height, BMI, low birth weight, lack of breastfeeding, single child, birth order, family size, birth season, preeclampsia, maternal smoking, childhood residency (urban or rural), parents' occupation and education, and race or ethnicity (8). Previous research has found that the menarche age varies across ethnicities and societies (9,10).…”
Section: Introductionmentioning
confidence: 99%